POSITIVE REINFORCEMENT AS A TRANSFORMING AGENT IN THE BEHAVIOR OF PRESCHOOL CHILDREN WITH TOD - Luci Freire de Duran, Maria; Dornelles da Silva , Carla (Revista Gênero e Interdisciplinaridade, 2025)
This article discusses Positive Reinforcement as a transformative agent in the behavior of children with Oppositional Defiant Disorder (ODD) at preschool age, and how it can be considered a differential strategy in emotional regulation and self-regulation during crises. To this end, the general objective is to describe how Positive Reinforcement can be a transformative agent in the behavior of children with ODD, providing them with an inclusive and socio-emotional experience. The specific objectives are to enable parents to become aware of the importance of positive reinforcement in the psychosocial and emotional development of children, improving affective and social relationships. To explain how the experiences and modeling of positive reinforcement that parents offer to their children shape their behavior. To point out, through the analysis of positive reinforcement, how children can carry out their socio-emotional activities and actions in a pleasurable way. To this end, it is based on explanatory bibliographic research, focusing on identifying and explaining the causes of the phenomena studied. In line with this research, 15 publications on the subject were analyzed.